Laho visual inclusivity and its effects on public knowledge of Philippine indigenous culture - Delfin, Alejandro Julian T.
Philippine Indigenous culture has been absent in Philippine popular media within the last 5 years, with disputes coming up over the accuracy of presented visuals in fictitious television series that even remotely reference something related to indigenous Filipino elements.